Morphological routine proposal to extraction of highways in digital images of high resolution - Frigato, R. [UNESP]; Silva, Erivaldo Antonio da [UNESP] (My University, 2009)
This research proposes to apply techniques of Mathematics Morphology to extract highways in digital images of high resolution, targeting the upgrade of cartographic products. Remote Sensing data and Mathematical Morphological techniques were integrated in the process of extraction. Mathematical Morphology's objective is to improve and extract the relevant information of the visual image. In order to test the proposed approach some morphological operators related to preprocess, were applied to the original images. Routines were implemented in the MATLAB environment. Results indicated good performances by the implemented operators. The integration of the technologies aimed to implement the semiautomatic extraction of highways with the purpose to use them in processes of cartographic updating.
Keywords: Cartographic updating; Extraction; High resolution images; Mathematics morphological; Remote sensing; High resolution image; Mathematics morphology; MATLAB environment; Morphological operator; Original images; Relevant informations; Remote sensing data; Mathematical morphology; Image processing